"Parenting Beyond the Veil": The Continued Parenting Relationship After a Child's Death Due to Cancer. (November 2021) - Denhup, Christine
Background: Childhood cancer is the leading cause of illness-related death, leaving thousands of parents to experience bereavement. This article presents select findings about the nature of the continued parenting relationship, which is an essential theme of the parental bereavement experience.Method: Heideggerian phenomenology provided the philosophical underpinnings of this study, which aimed to describe the lived experience of bereaved parents who experienced the death of a child due to cancer.Van Manen's (1997) method guided data collection and analysis. Six parents participated in interviews to share what it has been like for them since their child's death. The researcher wrote analytic memos, documented detailed field notes, and used a member checking process to ensure trustworthiness of findings.Results: A structure of the lived experience of parental bereavement emerged, which included the essential theme of the continued parenting relationship. The parenting relationship continues throughout a parent's lifetime in spite of the child's physical absence, albeit in a different manner. This different nature of parenting is known as parenting beyond the veil . Bereaved parents continue to parent beyond the veil by engaging in meaningful activities, seeking activities that strengthen a deep connection with the child, and being open to comforting signs that enhance their continued relationship.Discussion: Parents believe sharing their experience can help nurses and other professionals understand the importance of their continued parenting relationship and their need to parent beyond the veil so that they can provide high quality care to bereaved parents in the future.